2008
DOI: 10.1080/10641260701681847
|View full text |Cite
|
Sign up to set email alerts
|

Community-Based Stock Enhancement and Fisheries Management of the Japanese Flounder in Fukushima, Japan

Abstract: In Fukushima Prefecture, one million hatchery-reared juvenile Japanese flounder Paralichthys olivaceus have been released annually in the stock enhancement program since 1996. A community-based management system is used for this flounder fishery, where fishers pay 5% of their annual landings to operate the stock enhancement program. Also, since 1993, fishers have consented not to catch flounder <30 cm total length to maximize economic gains from the investment in stock enhancement. Our fish market surveys reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 8 publications
0
20
0
Order By: Relevance
“…The Sendai Bay-Joban area is highly productive for Japanese flounder, possibly resulting in high stocking effectiveness (Fujita et al 1993, Tomiyama et al 2008a, with an annual commercial catch of this species of >1000 t in Miyagi, Fukushima, and Ibaraki Prefectures from 2006 to 2008 (Kurita et al 2010). The present study demonstrated the 2 predominant food items (anchovy and sandlance) for Japanese flounder in this area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Sendai Bay-Joban area is highly productive for Japanese flounder, possibly resulting in high stocking effectiveness (Fujita et al 1993, Tomiyama et al 2008a, with an annual commercial catch of this species of >1000 t in Miyagi, Fukushima, and Ibaraki Prefectures from 2006 to 2008 (Kurita et al 2010). The present study demonstrated the 2 predominant food items (anchovy and sandlance) for Japanese flounder in this area.…”
Section: Discussionmentioning
confidence: 99%
“…Because this fishery is managed to restrict the landing of small Japanese flounder (< 30 cm total length [TL]; Tomiyama et al 2008a), the 4640 individual wild and released Japanese flounder sampled at the fish markets were ≥30 cm TL. Location of capture of these samples was recorded by asking the fishermen who caught the landed samples or by inferring from the operation area of each fishery community.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, N. hirame infection causes behavioural changes in juvenile P. olivaceus which may enhance predation risk (Shirakashi et al ., 2008). The effects of N. hirame infection on the P. olivaceus stock, however, have been considered not to be serious because of the stable high commercial catch of P. olivaceus in this water, >400 t in 1998–2002 (Tomiyama et al ., 2008 b ) during high infection levels (Fig. 2) and because of the high stocking effectiveness (Fujita et al ., 1993; Tomiyama et al ., 2008 b ).…”
Section: Discussionmentioning
confidence: 99%
“…Host body L T was assigned to four classes of 150–299, 300–399, 400–499 and ≥500 mm, as above. The cumulative landed number of 1 and 2 year‐old wild and released P. olivaceus from September to December, in that year, estimated from the fish market surveys (Tomiyama et al ., 2008 b ) was used as the index of S HP . Parasite mean intensity ( n host −1 ) × S HP × parasite prevalence (%) ×10 −2 in winter of the previous year was used to estimate S PP .…”
Section: Methodsmentioning
confidence: 99%
“…Such transformations are facilitated where the number of decision makers is small, and their interests are well aligned with those of the key stakeholders and by supportive external arrangements (Ostrom, 1990). The transformed institutional arrangements can be far more effective at regulating resource use than those previously in place, and this may play a greater role in determining outcomes than the release of cultured fish per se Drummond, 2004;Tomiyama et al, 2008).…”
Section: Dynamic Interactionsmentioning
confidence: 98%